Range of motion and rubber ball grasping therapy for improving upper limb function in patient with ischaemic stroke - Riyani Wulaningsih; Dian Hudiyawati; Sumarno Adi Subrata (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Ischemic stroke can impair hand and arm movements, significantly impacting a patient's ability to perform daily activities and consequently reducing their quality of life. A combined approach of range of motion (ROM) exercises and rubber ball gripping therapy offers a potential avenue for rehabilitation. This combined therapy aims to strengthen muscles, maintain joint flexibility, and retrain movement patterns. Regularly applying this therapy is anticipated to accelerate patient recovery and promote independent function. Purpose: To investigate the effectiveness of a combined range of motion exercise and rubber ball gripping in enhancing arm muscle strength in patients following an ischemic stroke. Method: A comparative study was conducted involving two groups: an intervention group receiving the combined therapy and a control group that did not. Upper extremity muscle strength was assessed in both groups before and after the intervention period using a handgrip dynamometer and clinical scales (MRC scale and MSTS score). Results: The study demonstrated a significant increase in upper extremity muscle strength in the intervention group compared to the control group (p<0.05) as measured by the handgrip dynamometer. These findings indicate that combining ROM therapy and rubber ball gripping is an effective strategy for improving muscle strength in patients after an ischemic stroke. Conclusion: The combination therapy of ROM exercises and rubber ball gripping can be considered an effective rehabilitation method for improving upper extremity muscle strength in patients with ischemic stroke. This study provides valuable evidence for medical professionals in developing more effective rehabilitation strategies for stroke patients.